The Similarities and Differences Between Children’s Mother Tongue Acquisition and Chinese Acquisition of Foreign Adults and Their Enlightenment to International Chinese Teaching - Lu, Hua; Li, Yecai (Journal of Social Science and Humanities, 2024)
By comparing and analyzing the similarities and differences between children's mother tongue acquisition and adults' foreign language acquisition, it reveals the common law in the process of language acquisition, and provides inspiration for international Chinese teaching. It is found that children's mother language acquisition and adults' foreign language acquisition are in common in the synchronous development, creative use, language strategies and other aspects. The paper puts forward six enlightenment of international Chinese teaching from the aspects of context support, tolerating mistakes, encouraging creative use, strengthening the training of written language system, and enriching the cultural resource base.